Primitive Interaction Design - Hoshi, Kei.; Waterworth, John.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
Interaction design is acknowledged as an important area of study, and more especially of design practice. Hugely popular and profitable consumer devices, such as mobile phones and tablets, are seen as owing much of their success to the way they have been designed, not least their interface characteristics and the styles of interaction that they support. Interaction design studies point to the importance of a user-centred approach, whereby products are in principle designed around their future users$1 (Bneeds and capacities. However, it is the market, and marketing, that determine which products are available for people to interact with and to a great extent what their designed characteristics are. Primitive Interaction Design is based on the realisation that designers need to be freed from the marketplace and industry pressure, and that the usual user-centred arguments are not enough to make a practical difference. Interaction designers are invited to cast themselves as (3z(Bsavages(3y(B, as if wielding primitive tools in concrete physical environments. A theoretical perspective is presented that opens up new possibilities for designers to explore fresh ideas and practices, including the importance of conscious and unconscious being, emptiness and trickery. Building on this, a set of design tools for primitive design work is presented and illustrated with practical examples. This book will be of particular interest to undergraduate and graduate students and researchers in interaction design and HCI, as well as practicing interaction designers and computer professions. It will also appeal to those with an interest in psychology, anthropology, cultural studies, design and the future of technology in society.s
Preface -- Part 1:Motivations and Inspirations -- Why Primitive Interaction Design -- Being Through Interaction -- Part 2: Theories and Foundations -- Savage and Trickster -- Emptiness, Nothingness and the Interval in Between- Unconscious Interaction and Design -- Part 3: Design Untamed -- The Designer as Savage -- Primitive Interaction Design: Methods -- Primitive Interaction Design: Examples -- Towards a New Culture of Interaction Design.
Keywords: User interfaces (Computer systems).; Graphic design; Psychology; Application software; User Interfaces and Human Computer Interaction; Interaction Design; Psychology, general; Computer Appl. in Social and Behavioral Sciences